(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In an era marked by rapid globalization and technological advancements, higher education institutions (HEIs) are compelled to innovate their marketing strategies to remain relevant and competitive. Uzbekistan, with its unique blend of historical richness and modern aspirations, faces distinct challenges in this domain. This article delves into the transformative pathways that HEIs in Uzbekistan can embark upon to navigate the intricacies of modern educational marketing. By synthesizing contemporary research, challenges, and potential solutions, this comprehensive exploration offers a roadmap for Uzbekistani HEIs to not only enhance their domestic appeal but also to position themselves as coveted choices for international students.